Improving Biology Learning Outcomes Through the Application of Entry Behavior in Intervertebrate Material in Senior High Schools - Sulastri, Eka; Ugwuoti, Osita (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to determine the improvement in student Biology learning outcomes through the implementation of Entry Behavior in class X at Public High School 1 West Bajeng, Gowa Regency. Methodology: This research is Classroom Action Research. The research location is at Public High School 1 West Bajeng which is located in Gowa Regency. The research subjects were 36 class X 4 students. This classroom action research procedure was carried out in two cycles, namely cycle I and cycle II. Each cycle consists of four stages, namely Planning, Action, Observation and Reflection. Main Findings: Completeness of learning outcomes in cycle I was 61% which met the minimum completeness criteria and overall from 36 students the average score obtained was 73.88 or on a descriptive scale categorized as sufficient, and there was an increase in cycle II which was 92% which met the minimum completeness criteria and overall from the 36 students the average score obtained was 85 or on a descriptive scale categorized as good. Implementation of learning by applying Entry Behavior in general can improve Biology learning outcomes because it has met the Minimum Accomplishment Criteria specified in the Biology subject Animalia material in class X 4 of Public High School 1 West Bajeng, Gowa Regency. Novelty/Originality of this study: The focus on the application of Entry Behavior (initial behavior) in Intervertebrate material in class X 4 at Public High School 1 West Bajeng, Gowa Regency.